(untitled) (Journal of Human Sciences, 2021)
This research is summarized in that it shows the secrets of obeisance inclucled in Surat ALsajdaah.It is concerned with obeisance and ALL its meanings and discovers the judgment and summon in obeisance, obeisance is glorified worship is not spint except for ALLah alone. Whoever is seized by devils obeisance will be adorned for him other than allah ,and whoever arrogates to abeisance to ALLah in this world ,he will not be able to obeisance in the after life if he colled for him.And the devil if he som Adams son obeisance he retire tocry. Obeisonce to ALLah is one of thechar acteris of believers who want ALLah,s pleasure the Surah collected from topics that necessitate obeisance in the hands of glory these topics are: The creation of man is one of the greatetst evidence of the power of almighty ALLah akdit o calls for obeisance, the creation of the heavens.the earth, manag the matter between them ,prescience and AL.Shahada is one of the greatest summons to obeisance and fear of ALLah almighty and the death thath Adams son was required to , and man would not be able to understand ,guidance is for all creat ues and the destruction of the first centuries this is a great work that almighty ALLah wipes out of all people ,it also calls for abeisance.there for, we find all that topics of the surah as a call to abeisance.